Milenialisme dan Covid-19: Milenialism And Covid-19 - Jadi Sampurna Lima (Reformed Center for Religion and Society, 2020)
The Covid-19 pandemic in the blink of an eye has radically changed the world as we know it. In a depressive atmosphere like this themes of doomsday or end of time naturally surfaces. This paper discusses the eschatological options of Christian beliefs and how they can contribute to the wider community. The eschatological discourse would be limited to three options with respect to the realization of God’s rule on earth, namely: premillennialism, postmillennialism and amillennialism in relation to the crisis of the times, the basic longings of humanity, and the reality of power. This paper tries to show how amillennialist eschatology can help Christians realize their social responsibility on the one hand, and on the other hand realize their limitations and mortality, while not losing hope in difficult conditions such as in pandemic times. This research employs hermeneutics and dogmatic studies to reach its aim. Keywords: Covid-19; doomsday; parousia; apocalypse; eschatology